2019
DOI: 10.1093/icvts/ivz255
|View full text |Cite
|
Sign up to set email alerts
|

Poor ventilatory efficiency during exercise may predict prolonged air leak after pulmonary lobectomy

Abstract: Poor ventilatory efficiency, defined as the increase in minute ventilation relative to carbon dioxide production during exercise (VE/VCO2 slope), may be associated with dynamic hyperinflation and thereby promote the development of prolonged air leak (PAL) after lung resection. Consecutive lung lobectomy candidates (n = 96) were recruited for this prospective two-centre study. All subjects underwent pulmonary function tests and cardiopulmonary exercise testing prior to surgery. PAL was defined as the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…The risk of CPC tended then to increase with the steepness of the slope, with a higher risk in patients with a E/ CO 2 slope >40. Our study did not establish any association between the V.E/V.CO 2 slope and the occurrence of prolonged air leak or other particular complications, as mentioned in Brat et al [ 18 ]. We showed that V.O 2peak is significantly reduced in patients with ventilatory insufficiency, suggesting reduced exercise capacity in these patients.…”
Section: Discussioncontrasting
confidence: 66%
“…The risk of CPC tended then to increase with the steepness of the slope, with a higher risk in patients with a E/ CO 2 slope >40. Our study did not establish any association between the V.E/V.CO 2 slope and the occurrence of prolonged air leak or other particular complications, as mentioned in Brat et al [ 18 ]. We showed that V.O 2peak is significantly reduced in patients with ventilatory insufficiency, suggesting reduced exercise capacity in these patients.…”
Section: Discussioncontrasting
confidence: 66%
“…The same CPET protocol was used as in our previous published studies [ 11 , 12 ]. Briefly, each patient underwent preoperative spirometry, D LCO assessment and CPET.…”
Section: Methodsmentioning
confidence: 99%
“…PPC were recorded prospectively from the first 30 post-operative days or from the hospital stay. The PPC were defined similarly to previous studies [ 9 , 11 , 12 , 14 ] and included: respiratory failure (requiring noninvasive ventilation or intubation plus invasive mechanical ventilation); acute respiratory distress syndrome (bilateral chest radiograph infiltrates not due to fluid overload or cardiac failure plus partial pressure of oxygen in arterial blood/inspiratory oxygen fraction ( P aO 2 / F IO 2 ) <300); tracheostomy; pneumonia (chest radiograph infiltrates plus at least two of the following signs: purulent sputum or fever or leukocytosis/leukopenia) and atelectasis (chest radiograph signs plus urgent bronchoscopy with removal of mucus plug). 30-day mortality and hospital and ICU length of stay (LOS) were also monitored.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8] During the past decade, studies on preoperative evaluation for lung surgery have found an association between the VE/VCO 2slope and both mortality [9][10][11][12] and perioperative pulmonary complications. [12][13][14] An algorithm for preoperative stratification of patients' risk of perioperative complications has been proposed, that incorporates both VO 2peak and ventilatory efficiency. 2 Patients in the moderate risk group (VO 2peak ¼ 10-20 mL/ kg/min), are suggested to be further risk stratified into low-moderate or moderate-high groups, based on a VE/ VCO 2 -slope less than or more than 35, respectively.…”
Section: See Commentary On Page XXXmentioning
confidence: 99%
“… 6 , 7 , 8 During the past decade, studies on preoperative evaluation for lung surgery have found an association between the VE/VC o 2 -slope and both mortality 9 , 10 , 11 , 12 and perioperative pulmonary complications. 12 , 13 , 14 …”
mentioning
confidence: 99%